Laser-assisted lateral optical fiber processing for selective infiltration - Zhang, Betty Meng (2014)
We propose a new technique to perform precise selective infiltration of an air hole in the photonic crystal fiber (PCF). To carry out the infiltration process, the end face of the PCF is covered by a mask, which is fabricated by femtosecond laser inscription from the lateral direction. This proposed method overcomes the conventional limitation of maximum mask thickness. An analytical model is further proposed and demonstrated accurate determinations of the fabricated channel diameter in the mask.